Presence of GH1 and absence of GHRHR gene mutations in a large cohort of Argentinian patients with severe short stature and isolated GH deficiency - Juanes, Matías Hernan (2013)
The prevalence of GH1 gene alterations is around 20% in patients with severe isolated growth hormone deficiency (IGHD) [...]